Supply Chain Reliability and International Economic Growth: Impacts of Disruptions like COVID-19 - Rajeev K. Goel; James W. Saunoris; Srishti S. Goel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Reliable supply chains are crucial to the productivity and economic growth of nations. Despite the recognition of its importance, formal research on the contribution of supply chain logistics, including the relative impacts across different logistics dimensions, is less. The importance of supply chains has been recently been brought to the forefront in the wake of the challenges posed by the coronavirus crisis. This paper uses data over a recent decade for more than 130 nations to examine the relative effects of the different aspects of supply chain logistics on economic growth. Placing the empirical framework in a standard growth model, results show that improvements in the aggregate supply chain logistics performance yield positive growth dividends. These dividends are also present in most disaggregated dimensions of logistics, with the performance of the timeliness of shipments having the greatest positive impact on growth. The growth impacts of investment, labor growth, labor quality, are positive and in line with the extant literature. A simulation exercise discussed some supply chain disruption scenarios and their growth implications that could provide useful for nations in planning for the challenges posed by the COVID-19 crisis.
Keywords: O40; L80; L91; 330; economic growth; supply chain; logistics; infrastructure; disruptions; coronavirus